IFN-γ-Licensed Mesenchymal Stem Cells Are More Susceptible to Death when Exposed to Quorum-Sensing Signal Molecule OdDHL and Less Effective in Inhibiting the Growth of Pseudomonas aeruginosa - Marielly Reis Resende Sousa; Amandda Évelin Silva-Carvalho; Maurício Gonçalves da Costa Sousa; Danilo César Mota Martins; Emãnuella Melgaço Garcez; Luma Dayane de Carvalho Filiú Braga; Juliana Lott de Carvalho; Tanise Vendruscolo Dalmolin; Taia Maria Berto Rezende; Felipe Saldanha-Araujo (Stem Cells International)
Currently, a series of licensing strategies has been investigated to enhance the functional properties of mesenchymal stem cells (MSCs). Licensing with IFN-γ is one of the most investigated strategies for enhancing the immunosuppressive potential of such cells. However, it is not yet known whether this licensing strategy could interfere with the ability of MSCs to control bacterial growth, which may be relevant considering their clinical potential. In this study, we compared the antimicrobial potential of IFN-γ-licensed and unlicensed MSCs by exposing them to Pseudomonas aeruginosa and its quorum-sensing inducer molecule OdDHL. Our data show that—when challenged with OdDHL—IFN-γ-licensed and unlicensed MSCs present increased levels of the antimicrobial HAMP transcript, but that only IFN-γ-licensed MSCs undergo modulation of CASP1 and BCL2, entering apoptosis. Furthermore, we demonstrate that only IFN-γ-licensed MSCs show modulation in genes involved in apoptosis and tend to undergo cell death when cultured with P. aeruginosa. As a consequence, IFN-γ-licensed MSCs showed lower capacity to control bacterial growth, compared to unlicensed MSCs. Taken together, our observations reveal an increased susceptibility to apoptosis of IFN-γ-licensed MSCs, which compromises their potential to control the bacterial growth in vitro. These findings are relevant to the field of cell therapy, considering the potential applicability of MSCs.